(untitled) - Hornyak, Timothy N. (Tokyo, 2006)
Loving the Machine attempts to answer this fundamental query by looking at Japan's historical connections with robots, its present fascination and leading technologies, and what the future holds. Through in-depth interviews with scientists, researchers, historians, artists, writers and others involved with or influenced by robots today, author Timothy N. Hornyak looks at robots in Japan from the perspectives of culture, psychology and history, as well as technology; and brings understanding to an endlessly evolving subject. From the Edo-period humanoid automatons, through popular animation icons and into the high tech labs of today's researchers into robotic action and intelligence, the author traces a fascinating trail of passion and development.
Keywords: Robotics,Robot; Design and construction,Thiết kế và xây dựng; Japan,Nhật Bản